Occurrence and molecular confirmation of lumpy skin disease among Vechur cattle in Kerala - R. Venkata Manoj; P.V. Tresamol; P. Preena; M. Manoj; R. Anoopraj; K. Justin Davis; V.H. Shyma; K. Vijayakumar (Journal of Veterinary and Animal Sciences)
Lumpy skin disease (LSD) is a notifiable disease caused by LSD virus belonging to the family Poxviridae and Capripoxvirus genus. The disease is characterised by fever, lymphadenopathy and presence of skin nodules. This article reports the occurrence of lumpy skin disease among Vechur cattle and its molecular confirmation. Two heifers in a Vechur farm were presented with elevated body temperature and nodules of varying sizes on the skin of abdomen and thorax region. Polymerase chain reaction was performed with primers targeting the viral attachment protein, P32 using DNA extracted from skin nodules which yielded amplicons of 192 bp size specific for LSD virus. Haematological and serum biochemical parameters were found to be within in the normal ranges. Histopathology of skin nodules revealed pyogranulomatous myositis and fibrinous vasculitis. Successful treatment was provided with broad spectrum antibiotic, anti-inflammatory drugs and topical antiseptic application. The findings of present study warrant the need for adopting control measures against LSD, including vector control and vaccination in the indigenous breeds of cattle like Vechur.